Downregulation of TET1 Promotes Bladder Cancer Cell Proliferation and Invasion by Reducing DNA Hydroxymethylation of AJAP1 - Yan, Yi-lin; Huang, Zheng-nan; Zhu, Zhen; Cui, Yang-yan; Li, Mei-qian; Huang, Rui-min; Yan, Jun; Shen, Bing (Frontiers in Oncology, 2020)
Ten-Eleven Translocation 1 (TET1) is a member of methylcytosine dioxygenase, which catalyzes 5-methylcytosine (5mC) to 5-hydroxymethylcytosine (5hmC) to promote the demethylation process. The dysregulated TET1 protein and 5hmC level were reported to either suppress or promote carcinogenesis in a cancer type dependent manner. Currently the role of TET1 in the development of urinary bladder cancer (UBC) and its underlying molecular mechanisms remain unclear. Herein, we found that TET1 expression was downregulated in UBC specimens compared with normal urothelium and was inversely related to tumor stage, grade and overall survival, suggesting its negative association with UBC progression. TET1 silencing in UBC cells increased cell proliferation and invasiveness while the ectopic expression of wild-type TET1-CD, but not its enzymatic inactive mutant, reversed these effects and suppressed tumorigenicity in vivo. In addition, as a direct regulator of TET1 activity, vitamin C treatment increased 5hmC level and inhibited the anchorage-independent growth and tumorigenicity of UBC cells. Furthermore, we found that TET1 maintained the hypomethylation in the promoter of the AJAP1 gene, which codes for Adherens junctions-associated protein 1. The downregulation of AJAP1 reversed TET1-CD-induced nuclear translocation of β-catenin, thus inhibiting the expression of its downstream genes. In human UBC specimens, AJAP1 is frequently downregulated and positively associated with TET1. Notably, low expression levels of both TET1 and AJAP1 predict poor prognosis in UBC patients. In conclusion, we found the frequently downregulated TET1 level reduces the hydroxyl-methylation of AJAP1 promoter and subsequently activates β-catenin signaling to promote UBC development. The downregulation of both TET1 and AJAP1 might be a promising prognostic biomarker for UBC patients.